PKM PENCEGAHAN COVID 19 DI ERA NEW NORMAL PADA MASYARAKAT DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Kasumayanti, Erma; Sulastri Juwita, Dewi; Mayasari, Endang (COVIT (Community Service of Tambusai), 2021)
The Corona virus can cause disorders of the respiratory system, acute pneumonia and even cause death. This virus spreads very quickly and has spread to almost all countries, including Indonesia. Preventive efforts in the health protocol implemented by the community in breaking the chain of transmission of COVID 19 during the New Normal period, namely by getting used to using masks, washing hands with soap (handsanitanizer), maintaining distance (social distancing), staying away from crowds and avoiding traveling outside the area, especially the areas that have been declared as red zones. In Pulau Jambu Village, there is still low public awareness of compliance in implementing health protocols in the new normal era in preventing Covid-19. Many people still don't use masks in public places, don't pay attention to social distancing and still have low awareness of washing hands. Health promotion regarding the prevention of Covid-19 is carried out to increase public knowledge and awareness to decide the transmission of the Covid-19 virus. This activity starts from the preparation stage, implementation of activities. After the PKM was carried out on July 17 2020. The result was that there was an increase in public knowledge about how to prevent Covid 19. With this PKM activity it is hoped that the community can increase their awareness to improve health and prevent disease. Keywords: Covid -19, New Normal Era, Prevention